The Effect of Using Distance E-Learning on Improving the Level of Knowledge Outcome In The Course Of Sports Injuries among Students of the Faculty of Sports Sciences at Mutah University - Sha’lan, Maen Ahmad Mahmoud; Al-Zaghilat, Muhannad Odeh; Al Madanat, Amjad Najeeb (Dirasat: Educational Sciences, 2023)
Objectives: The study sought to determine the impact of distance e-learning on enhancing students’ knowledge of sports injuries at Mutah University’s Faculty of Sports Sciences. Methods: The experimental approach was employed, which had a two-way design with an experimental and a control group, comparing pre- and post-measurements for each group and then comparing the two groups. (118) sports injury students from the College of Sports Sciences, Mutah University, first-semester 2020/2021, were the study population. 50 students were chosen randomly to serve as the study sample, and they were split into two groups: 25 students, as the experimental group, used the distant website for self-directed e-learning, while the remaining students were the control group. The experimental group met twice weekly for six weeks to study the sports injury course’s vocabulary; the control group met twice weekly for six weeks to learn the same vocabulary through more conventional means. A test with 25 multiple-choice questions was developed to evaluate the students’ cognitive growth. Results: After six weeks of distance education involving the website in presenting a course on sports injuries, learning outcomes were found to be higher for students in the experimental group, with an arithmetic mean of 69% and a standard deviation of 13%, compared to control group participants in the post-measurement of cognitive results with an arithmetic mean (58%) and a standard deviation (13%) Conclusions: The study suggests employing e-learning to teach the language of the sports injury course via the website.